Revitalized Johor Bahru waterfront : visitors' center - 176399 Cheu, Michael Teck Lian (SkudaI : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2008